Inégalités et pandémie dans les communautés autochtones au Paraguay - Andréanne Brunet-Bélanger (Cahiers des Amériques Latines)
This article discusses the measures introduced by Paraguay to respond to the health crisis between March and December 2020 and problematizes its impact on indigenous communities. Starting from a historicization of the origins of inequalities, it demonstrates that the marginalization that Paraguayan indigenous communities are currently experiencing is the result of a historical and institutional continuity that is rooted in a logic of dispossession of indigenous people and their territory. We argue that the interaction between previous structural conditions and the political choices emanating from the struggle against Covid-19 has not allowed for an institutional change in these relationships. Indeed, in Paraguay, the unprecedented health crisis and governmental responses accelerated the pre-existing trajectories affecting indigenous communities, resulting in institutional continuity in the formulation of public policies.